[Frederick Street, Trinidad] - (:unkn) unknown (My University, 2010)
Pedestrians crossing Frederick Street, downtown Port of Spain.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Streets--Trinidad and Tobago; Pedestrians--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Bicycles--Trinidad and Tobago; Shopping--Trinidad and Tobago; Stores, Retail--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Signs and signboards--Trinidad and Tobago; Street-railroads--Trinidad and Tobago; Architecture--Trinidad and Tobago; Clocks and watches--Trinidad and Tobago; Children--Trinidad and Tobago; Frederick Street (Port of Spain)